The 2018 edition of the OECD PMR indicators and database: Methodological improvements and policy insights - Vitale, Cristiana (OECD Economics Department Working Papers, 2020)
This paper presents the latest edition of the OECD indicators of product market regulation (PMR), which measure regulatory stance in 35 OECD and 11 non-OECD countries. This update is based on a new methodology, which has been implemented to ensure that the PMR indicators maintain their relevance in the context of evolving insights from economic theory, modifications in the economic and business environment, and changes in the practice of regulation. The results show that most OECD countries have a regulatory stance that is reasonably competition-friendly, while the 11 non-OECD countries lag behind, though there is considerable variety across them